(untitled) (The Review of Diabetic Studies, 2024)
Introduction: Nursing is implicit in the healthcare transformation of the Saudi Vision 2030, but the swift shift to a decentralizing Health Cluster structure and higher clinical demands have caused a considerable psychological strain on the workforce. The concept of burnout, which occurs when nurses are emotionally exhausted, depersonalized, and their personal accomplishment is lower, is a significant risk to patient safety and nurse retention in the Kingdom. The national healthcare requirement can only be maintained by understanding the special stressors experienced by both Saudi national and expatriate nurses. Objective: The purpose of this systematic review is to assess the prevalence, causes, and outcomes of burnout related to mental health amongst Nurses who work in the Saudi Healthcare System as part of the Vision 2030 transformation phase. Method: The peer-reviewed literature search was done in systematic searches to databases such as PubMed, CINAHL, Scopus, and the Saudi Digital Library (SDL). The identification included the literature published between 2020 and 2026 to reflect the post-pandemic environment and the height of the reforms in the Vision 2030. In line with the PRISMA criteria, studies were excluded in case they did not use validated instruments like Maslach Burnout Inventory (MBI). The data collected was extracted on 32 selected studies, and a narrative synthesis was applied. Conclusion: This is a widespread problem of burnout in the Saudi nursing industry that should be systemically addressed. Although cultural and spiritual resilience can act as a special buffer, it cannot substitute the necessity of organizational reforms. The Saudi Health Clusters, in order to meet the objectives of the Vision 2030, will need to focus on caring about the caregiver by providing structured mental health care, decreasing administrative workloads, and inclusive leadership to have a healthy and stable workforce of nurses.